Case Report: Two cases of chronic active Epstein-Barr virus disease presenting as refractory sinusitis - Wang, Puyu; Dong, Dong; Huang, Shuman; Wang, Linyuan; Zhang, Hui; Li, Yuanyuan; Zhao, Yulin (Frontiers in Immunology, 2025)
BackgroundChronic active Epstein-Barr virus disease (CAEBV) is a systemic, progressive lymphoproliferative disorder caused by the Epstein-Barr virus (EBV) infecting T cells and/or natural killer (NK) cells. It exhibits both inflammatory and clonal proliferative characteristics. Given the rarity of this disease, there is a relative scarcity of diagnostic and therapeutic expertise. Additionally, the clinical manifestations are varied and affect multiple systems, which can lead to cases being either missed or misdiagnosed. Consequently, the prognosis is often poor.Case presentationThis article reports two cases of systemic CAEBV presenting as refractory sinusitis. Case one is an 18-year-old male, and case two is a 22-year-old female. The main symptoms of both patients were intermittent fever, nasal congestion and bloody nasal discharge for more than six months. Pathological examination indicated EBV-associated lymphoproliferative disease. The diagnosis of systemic CAEBV was established on the basis of clinical presentation and pathological findings and EBV DNA test. Both patients showed poor response to immunotherapy or chemotherapy and progressed to hemophagocytic lymphohistiocytosis (HLH). Case one was eventually cured by Chimeric Antigen Receptor T-Cell Immunotherapy (CAR-T). In case two, the condition deteriorated rapidly and she died of multiple organ failure and septic shock after hematopoietic stem cell transplantation.ConclusionThis rare case report describes two cases of systemic CAEBV presenting as refractory sinusitis. The report also shows the potential of CAR-T as a treatment for CAEBV. We comprehensively reviewed the diagnostic and therapeutic trajectories of both patients from disease onset, hoping to provide reference for clinical practice.